Project-Based Learning Assistance to Improve Learning Independence of Children in Orphanages - A. Zebar; Tri Auri Yanti; Muhammad Dekar (Outline Publisher, 2026)
This community service activity addresses the persistent issue of low learning independence among children living in social welfare institutions, who often rely heavily on passive instructional methods and direct supervision. The primary objective is to enhance the self-regulated learning capacities of orphanage residents through structured project-based mentoring. The methodology employed a participatory service-learning approach involving thirty adolescents between the ages of twelve and fifteen. Data collection was conducted using self-reliance questionnaires, observation rubrics, and project outcome evaluations to measure shifts in attitudes and social-cultural dynamics. The findings indicate a significant transformation in the participants' learning behaviors, with a notable increase in time management skills and personal initiative. All participant groups successfully completed their assigned projects, ranging from digital content creation to simple environmental management, demonstrating a shift from dependence to proactive engagement. Furthermore, the initiative successfully established a new institutional framework for caregivers to facilitate more interactive and autonomous learning environments. In conclusion, the project-based mentoring model provides a robust solution for fostering autonomy and problem-solving skills in marginalized youth. While the program faced logistical challenges, its success suggests that empowering children with tangible responsibilities can effectively break the cycle of educational passivity. Future iterations of this program should explore the integration of digital platforms to sustain these gains and broaden the socio-economic impact for orphans transitioning to independent living.